# Solve for y -6/5y-5=1/5y-4/3 -65y-5=15y-43
Simplify each term.
Combine y and 65.
-y⋅65-5=15y-43
Move 6 to the left of y.
-6y5-5=15y-43
-6y5-5=15y-43
Combine 15 and y.
-6y5-5=y5-43
Move all terms containing y to the left side of the equation.
Subtract y5 from both sides of the equation.
-6y5-5-y5=-43
Combine fractions with similar denominators.
-5+-6y-y5=-43
Subtract y from -6y.
-5+-7y5=-43
Move the negative in front of the fraction.
-5-7y5=-43
-5-7y5=-43
Move all terms not containing y to the right side of the equation.
Add 5 to both sides of the equation.
-7y5=-43+5
To write 5 as a fraction with a common denominator, multiply by 33.
-7y5=-43+5⋅33
Combine 5 and 33.
-7y5=-43+5⋅33
Combine the numerators over the common denominator.
-7y5=-4+5⋅33
Simplify the numerator.
Multiply 5 by 3.
-7y5=-4+153
-7y5=113
-7y5=113
-7y5=113
Multiply both sides of the equation by -57.
-57⋅(-7y5)=-57⋅113
Simplify both sides of the equation.
Simplify -57⋅(-7y5).
Cancel the common factor of 5.
Move the leading negative in -57 into the numerator.
-57⋅(-7y5)=-57⋅113
Move the leading negative in -7y5 into the numerator.
-57⋅-7y5=-57⋅113
Factor 5 out of -5.
5(-1)7⋅-7y5=-57⋅113
Cancel the common factor.
5⋅-17⋅-7y5=-57⋅113
Rewrite the expression.
-17⋅(-7y)=-57⋅113
-17⋅(-7y)=-57⋅113
Cancel the common factor of 7.
Factor 7 out of -7y.
-17⋅(7(-y))=-57⋅113
Cancel the common factor.
-17⋅(7(-y))=-57⋅113
Rewrite the expression.
-1⋅(-y)=-57⋅113
-1⋅(-y)=-57⋅113
Multiply.
Multiply -1 by -1.
1⋅y=-57⋅113
Multiply y by 1.
y=-57⋅113
y=-57⋅113
y=-57⋅113
Multiply -57⋅113.
Multiply 113 and 57.
y=-11⋅53⋅7
Multiply 11 by 5.
y=-553⋅7
Multiply 3 by 7.
y=-5521
y=-5521
y=-5521
The result can be shown in multiple forms.
Exact Form:
y=-5521
Decimal Form:
y=-2.619047‾
Mixed Number Form:
y=-21321
Solve for y -6/5y-5=1/5y-4/3

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top